Genetic correlations between linear traits and milk production in Girolando cattle - Santos, Mateus Guimarães dos (2023)
Productive traits have always guided genetic improvement programs, such as milk, fat and protein production. Other features were implemented over time to achieve gains in profitability and productive longevity, examples are age at first calving and calving interval. However, the production systems, which for the most part are extremely complex and diverse, pose a greater challenge to the animals. These in turn, may show a drop in performance due to lack of morphology. Works on morphology, known as linear traits, are an old practice in already consolidated breeds such as Holstein, however in animals of the Girolando breed, studies are scarce. The inclusion of new traits in genetic improvement programs requires a prior study of the impact of these new traits on those already evaluated, such as milk production. Thus, the objective of this study was to describe genetic parameters for all linear traits evaluated by the breeding program of the Girolando breed and their correlations between them and milk production. The phenotypic data of the twenty-two linear traits and milk production were provided by EMBRAPA – Dairy Cattle. The single trait models used were previously tested and validated, for the genetic correlations, that were obtained through the correlation of the estimated genetic values. High heritabilities were found for body conformation traits and rump measurements, the lowest for locomotor system, and from low to high for mammary system traits. The correlations were higher between body conformation and hip measurements, between linear and locomotor system the highest number of negative and unfavorable correlations were found. For milk production, most of the correlations were between -0.3 to 0.3, denoting that there is a direct impact on milk production due to the selection of sires for linear traits. In general terms, there is enough genetic variability for the practice of selection for the twenty-two linear traits, nine pairs of unfavorable correlations were found, these must be taken carefully when choosing future sires Keywords: Genetic Correlations. Milk Yield. Selection